2009
DOI: 10.1051/0004-6361/200912917
|View full text |Cite
|
Sign up to set email alerts
|

Can gas in young debris disks be constrained by their radial brightness profiles?

Abstract: Disks around young stars are known to evolve from optically thick, gas-dominated protoplanetary disks to optically thin, almost gasfree debris disks. It is thought that the primordial gas is largely removed at ages of ∼10 Myr and indeed, only little amounts of gas have been deduced from observations for debris disks at ages of > ∼ 10 Myr. However, gas detections are difficult and often indirect, not allowing one to discern the true gas densities. This suggests using dynamical arguments: it has been argued that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 67 publications
2
36
2
Order By: Relevance
“…Such a radial profile that rises outward with a sharp outer edge contrasts with those derived for the archetypal disks Vega (Su et al 2005;Krivov et al 2006;Müller et al 2010;Sibthorpe et al 2010) and β Pictoris (Golimowski et al 2006;Thébault & Wu 2008;Krivov et al 2009;Vandenbussche et al 2010). In these disks, the derived geometrical optical thickness typically falls off with a moderate r −1.5 relationship beyond the peak value, i.e.…”
Section: Resultsmentioning
confidence: 67%
“…Such a radial profile that rises outward with a sharp outer edge contrasts with those derived for the archetypal disks Vega (Su et al 2005;Krivov et al 2006;Müller et al 2010;Sibthorpe et al 2010) and β Pictoris (Golimowski et al 2006;Thébault & Wu 2008;Krivov et al 2009;Vandenbussche et al 2010). In these disks, the derived geometrical optical thickness typically falls off with a moderate r −1.5 relationship beyond the peak value, i.e.…”
Section: Resultsmentioning
confidence: 67%
“…Dust grains also orbit with sub-Keplerian velocity but their pace depends on size and composition. Velocity difference between gas and dust induces grain migration within the disk (Takeuchi & Artymowicz 2001;Krivov et al 2009). Grains with angular velocities larger/smaller than that of the gas lose/gain angular momentum and drift inward/outward until they are in corotation with the gas.…”
Section: Discussionmentioning
confidence: 99%
“…Grains with angular velocities larger/smaller than that of the gas lose/gain angular momentum and drift inward/outward until they are in corotation with the gas. Based on their models, Krivov et al (2009) found that even in gaseous debris disks with gasto-dust mass ratio of 100, the grains' lifetime will be very limited -typically less than 2×10 4 yr -because collisions occur between radially drifting grains with unequal sizes. Applying these findings for the case of HD 21997, we conclude that the grains must be replenished and are of secondary origin.…”
Section: Discussionmentioning
confidence: 99%
“…We then follow the same procedure as in Thébault & Augereau (2005) and Krivov et al (2009) and record, at regularly spaced time intervals, the positions of all remaining particles. The disc's spatial structure is progressively obtained by adding up these instantaneous snapshots until all particles have been removed either dynamically or collisionally.…”
Section: Methodsmentioning
confidence: 99%